Al-Majusi contribution in the understanding of the cardiovascular system and blood circulation - Ghazali, Nazwan; Shuriye, Abdi Omar (IIUM Press, 2011)
The objective of this chapter is to represent AI-Majusi contributions in carduivascular system and blood circulation. The chapter refers to the main treatise entitled Kitab Kamil Sina 'ah Tibiyah, (The Complete Medical Art), written by Ali Ibn Abbas AI-Majusi, and other articles on cardiovascular system and blood circulation. The science ofthe heart and circulatory system took scientists centuries to comprehend and develop, providing us at the end, with what we know today. The chapter therefore, is an attempt to show how AIMajusi rectified certain concepts adapted by his predecesors on the same subject. Ali Ibn Abbas AI-Majusi was a Persian physician and psychologist (925-994 C) He was born in Ahvaz, Iran and The Complete Book of the Medical Art (Kitab Kamel AI-Sinaa AITibiyya) is his major work on the subject